Mechanical and light transmittance properties of high-performance translucent concrete. (December 2022) - Tahwia, Ahmed M.; Abdelaziz, Nirmen; Samy, Mohamed; Amin, Mohamed
Abstract: High-Performance Translucent Concrete (HPTC) is an innovative energy-saving building material, as it is a high-quality translucent concrete with high workability, superior mechanical properties, and good light transmittance. This paper investigates the performance of HPTC incorporated with plastic optical fibers (POF), its fresh properties, mechanical properties, and light transmittance performance. The data presented here refer to specimens of 21 mixtures divided into six main groups, the latter group upgraded to be ultra-high performance translucent concrete (UHPTC). Besides fresh concrete tests, bulk density, all-ages compressive strength, splitting tensile strength, flexural strength, bond strength, modulus of elasticity strength, and light transmittance as well as relations between light transmittance and mechanical properties were investigated in the HPTC hardened phase. Although the HPTC mechanical properties increase with increasing POF volume ratios and diameters, the light transmittance significantly increases with increasing POF volume ratios. In this paper, HPTC performs up to 21.35% light transmittance for specimens with a volume ratio of 4% POF and 2 mm POF diameter as well as good mechanical properties such as compressive strength of 54.30 MPa at 91 days. In addition, UHPTC performs up to 154.2 MPa compressive strength, 13.8 MPa tensile strength, 23 MPa flexural strength, 25.7 MPa bond strength, and 49.71 GPa modulus of elasticity, as well as 10.31 % light transmittance.